2017
DOI: 10.3389/fphar.2017.00361
|View full text |Cite
|
Sign up to set email alerts
|

Specific Combination of Salvianolic Acids As Core Active Ingredients of Danhong Injection for Treatment of Arterial Thrombosis and Its Derived Dry Gangrene

Abstract: Although single-targeting anti-platelet agents are used extensively in clinics, their limitations in resistance and bleeding have started a trend of combination therapy. Danhong injection (DHI) is a widely prescribed injection medicine for cardiovascular and cerebrovascular diseases in China. However, its precise clinical efficacy and functional components remain unexplored. In this study, we investigated the anti-thrombotic role and its chemical basis of DHI. In a photochemically-induced thrombosis model, DHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Subsequent in vitro and in vivo studies have confirmed that Sal-A inhibits ADP and collagen-induced platelet aggregation and arterial thrombus formation in mice [121][122][123][124] . Salvianolic acids, in particular Sal-A and Sal-C, are core components of Danhong injection exerting anti-thrombotic activity [125] . The cardiovascular actions of salvianolic acids have recently been comprehensively reviewed elsewhere [126] .…”
Section: Anti-thrombotic Effects Of Sal-a Its Derivatives and Preparmentioning
confidence: 99%
“…Subsequent in vitro and in vivo studies have confirmed that Sal-A inhibits ADP and collagen-induced platelet aggregation and arterial thrombus formation in mice [121][122][123][124] . Salvianolic acids, in particular Sal-A and Sal-C, are core components of Danhong injection exerting anti-thrombotic activity [125] . The cardiovascular actions of salvianolic acids have recently been comprehensively reviewed elsewhere [126] .…”
Section: Anti-thrombotic Effects Of Sal-a Its Derivatives and Preparmentioning
confidence: 99%
“…Thus, the results suggest that colloidal aggregation is not a major contributor to the inhibition of the specific binding of [ 3 H]2MeSADP by salvianolic acids. Additionally, the reports that SAA and SAC are more potent at ADP-induced than at thrombin-induced platelet aggregation 8 , 35 may also support a specific effect of these compounds.…”
Section: Resultsmentioning
confidence: 91%
“…Analysis of the components in the Dan-Hong injection and their pharmacodynamic effects has revealed that DSS, SAA, SAB, and HSYA are the main active ingredients [30,46,[49][50][51]. Therefore, a pharmacokinetic study of the these four active ingredients appeared to be reasonable and necessary.…”
Section: Discussionmentioning
confidence: 99%